Sharks and rays fisheries of the Bay of Bengal at the landing centers of Chittagong and Coxs Bazar, Bangladesh (Bangladesh Journal of Zoology, 2015)
The study was conducted on the species composition and percentage contribution of sharks and rays from two landing centers (Fishery ghat, Chittagong and BFDC fish harbour, Coxs Bazar) during 2011-2012 fiscal year. A total 10 species of sharks belonging to 3 families and 14 species of rays belonging to 8 families were recorded. Total landings of sharks and rays by weight were 382.67 MT of which 136.45 MT was sharks and 246.22 MT was rays. A total 479661 numbers of sharks and rays were landed of which 449133 were sharks and 30528 were rays but contribution of sharks and rays were 35.66% and 64.34%, respectively by weight. The highest landing was 70.94 MT in the month of October, 2011 and lowest landing was 6.05 MT in the month of January, 2012. The highest landing of shark species was Scoliodon laticaudus (84.52 MT) (22.09%) and lowest was Carcharhinus sorrah (0.01MT) and the maximum and minimum landing of rays species were Himantura uarnak (164.42MT) (42.97%) and Aetobatus narinari (0.03% MT), respectively.Bangladesh J. Zool. 41(1): 49-60, 2013